The effects of the interaction between irrigation and fertilization systems on the growth and productivity of tomato crop - Mohamed, Alaa Jamalaldeen Shreef; Ali, Osama Osman; Ibrahim, Yassir Mohamed; Abdalhi, Mohmed Abdallah Mohmed (Gezira Journal of Agricultural Science, 2026)
The study investigates the integrative effects of modern drip and traditional furrow irrigation techniques, and nitrogen fertilization strategy on tomato farms production under water-limited conditions in arid region northern Sudan. The research employs in a split-plot with a factorial subplot in a randomized completely block design with three replications, drip irrigation and furrow irrigation assigned as main plot treatments, and four N fertilizer application rates (0%, 60%, 80% and 100%) as subplots. The study tested the irrigation techniques performance, growth parameters, yield components and nutrient use efficiency. The analysis of irrigation techniques performance across irrigation methods shows a significant advantage for modern drip irrigation technique over furrow irrigation with the highest values of Christiansen Uniformity (CU = 87.6%) and Distribution Uniformity (DU = 78%).  The study results reveal significant impacts of average discharge, CV(Coefficient of Variation), CU and DU at 0.05 level of significant. Their results ranged from 3.45 l/h - 5.23 l/h, 3.03 - 6.33, 60.33% - 87.6% and 60.6% - 78%. The integration of SDI with 80% NFR in drip irrigation and FI with 100% NFR in furrow obtained maximum tomato yield as 25.73 fruit/plant and 12.40 fruit/plant and saved 20% of nutrient use. In other hand, considering the agronomy components and yield components, the most preferable integration may assigned to SDI with 80% NFR in drip irrigation and FI with 80% NFR in furrow for their high yield, better agronomy components, enhancement of yield components and increased nutrient use efficiency. The study presented profitable water and nutrient combination strategies, adoption of these strategies is a beneficial in water and nutrient -limited conditions in arid or similar regions.